Ecotourism Development Strategy of Bukit Jaddih Karst, Madura - Parmawati, Rita; Imaniyah, Rif'atul; Rokani, Lutvita Eka; Rajaguni, Muhammad Iqbal; Kurnianto, Agung Sih (Journal of Indonesian Tourism and Development Studies, 2018)
Bukit Jaddih karst in Bangkalan, Madura, is an ex-limestone mining location managed partially by individuals or community groups as tourism area. This study aims to develop sustainable strategies for Bukit Jaddih karst resources and ecotourism. Data were obtained from questionnaires given to 30 respondents consisting of visitors, miners, traders, society, and policymaker then being analyzed for the strategy on the development of tourism object. SWOT strategy was used to determine every aspect of tourism development (weight 0.00 to 1.00). Score are given in a rating where the rating indicates the level of importance. The IFAS analysis shows Bukit Jaddih karst has some dominant internal strengths, i.e. uniqueness, safety, cleanliness, access to food-stalls, and cellular networks covering tourist areas. However, tourist services in Bukit Jaddih karst are not good enough and indicated as dominant weakness. EFAS shows that Bukit Jaddih karst can provide employment opportunities for the surrounding community. The strategy of the Matrix analysis supports an aggressive growth policy (Growth Oriented Strategy), which is using the Strength Opportunities (SO) strategy and is applied based on the utilization of the opportunities of Bukit Jaddih karst ecotourism. The strategies to be developed are 1). Promotion through prints, TV, radio and social media; 2). Developing diversified tourism attractions; 3). Mapping the tourism potential of Bangkalan Regency; 4). Establishment of Tourism Awareness Group (Kelompok Sadar Wisata, Pokdarwis); 5). Training for local community as guide; 6). The establishment of Surabaya-Madura tourism package; 7). Establishment of regulations on the cleanliness, security, and comfort.Keywords: Bukit Jaddih karst, EFAS, IFAS, strategy, tourism development.